Heavy mineral constraints on Paleocene sand transport routes in the Faroe-Shetland Basin - Morton, A. C.; Ellis, D.; Fanning, M.; Jolley, D. W.; Whittham, A.
An integrated sandstone provenance study involving heavy mineral analysis, major element geochemistry of garnet, trace element geochemistry of rutile, detrital zircon age dating and palynofloral analysis has been undertaken on Paleocene (T10-T38) sandstones in hydrocarbon exploration wells in the Faroe-Shetland Basin. This study has led to the identification of four siliciclastic sand types, each with a different provenance, together with volcaniclastic detritus. Sand type I was mainly derived from basement lithologies (Lewisian and/or Moine/Dalradian) on the Orkney-Shetland Platform, either directly or indirectly through recycling. Sand type II was derived principally through recycling of the Triassic on the Orkney-Shetland Platform. Sand type III, which is commonly found in association with volcaniclastic material, is interpreted as having an origin on the western margin of the basin. Sand type IV represents recycled Carboniferous (Namurian- Westphalian) sandstones on the Orkney-Shetland Platform. Although the westerly-derived sand type (III) has a zircon age spectrum dominated by the Archaean, the pattern contrasts with that found in Archaean-derived Paleocene sandstones from the Kangerlussuaq region of East Greenland. Derivation from more local Archaean basement is therefore inferred: possibilities include the crust below the Faroe Islands, the Blosseville Kyst of East Greenland and the Wyville-Thomson Ridge. Palynofloral analysis indicates that sand type III is invariably found in association with the ‘Greenland flora’, providing further support for input from the west. Most of the terrigenous sand was supplied from the Orkney-Shetland Platform, but western input is seen locally at T10, T35-T36 and T38 levels.